2020
DOI: 10.1371/journal.ppat.1008663
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the path toward an HIV-1 vaccine into focus

Abstract: Why do we need a human immunodeficiency virus (HIV-1) vaccine in the age of antiretroviral therapy and preexposure prophylaxis?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In the case of AIDS, the capacity of immunodeficiency virus type 1 (HIV-1) to escape components of the human immune response through mutation, the debilitated response due to the HIV-1 tropism for cells involved in the immune response, and the proviral DNA integration as part of the virus life cycle are reasons why to date there are no effective anti-AIDS vaccines [ 17 , 18 ]. Antiretroviral therapy has been successful in reducing AIDS and HIV-1 infection-related mortality, but antiretroviral resistance through genetic variation of the virus and selection of escape mutants remains an issue.…”
Section: Introduction: Mistakes As Hallmark Of the Evolution Of Life And Of Present Day Virusesmentioning
confidence: 99%
“…In the case of AIDS, the capacity of immunodeficiency virus type 1 (HIV-1) to escape components of the human immune response through mutation, the debilitated response due to the HIV-1 tropism for cells involved in the immune response, and the proviral DNA integration as part of the virus life cycle are reasons why to date there are no effective anti-AIDS vaccines [ 17 , 18 ]. Antiretroviral therapy has been successful in reducing AIDS and HIV-1 infection-related mortality, but antiretroviral resistance through genetic variation of the virus and selection of escape mutants remains an issue.…”
Section: Introduction: Mistakes As Hallmark Of the Evolution Of Life And Of Present Day Virusesmentioning
confidence: 99%
“…In addition, Th-cell mediated immunity is important to promote a functional CD8 ? CTL response and prolong antibody immune responses leading to protection and viral load reduction (Abdulla et al 2019;Lopez Angel and Tomaras 2020). Development of new immunoinformatics tools for analysis of HIV-1 proteins and identifying their poly-functional T-cell epitopes, especially when used in combination with in vivo analyses, can improve the immunogen design for HIV-1 vaccines (Khairkhah et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the potential protective role of neutralizing antibodies in both animal and human models [ 216 ]. However, in the RV144 vaccine trial, IgG antibodies correlated with lower HIV-1 risk and were able to drive ADCC, ADCP and complement activation [ 79 , 217 ], underscoring the role of non-neutralizing effector functions in protective vaccination. In a recent study, HIV-specific antibodies demonstrated antibody-dependent neutrophil phagocytosis (ADNP) and ADCC functions in the genital tract [ 218 ].…”
Section: Mucosal Immunitymentioning
confidence: 99%